2019
DOI: 10.1017/ipo.2019.30
|View full text |Cite
|
Sign up to set email alerts
|

Opening the ‘Black Box’ of asylum governance: decision-making and the politics of asylum policy-making

Abstract: Complementing and challenging the existing literature on the Italian asylum crisis, this article develops an actor-centred approach to open the ‘black box’ of asylum governance, showing the constitutive effects of governance on the asylum issue. It then applies this approach to the case of the Veneto region in Italy during the recent ‘refugee crisis’. By doing so, the article, first, investigates the cognitive mechanisms that shape key actors’ asylum policy decisions. Drawing concepts and ideas from framing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Many interviewees, if explicitly asked so, reported that they remembered some spontaneous anti-migrant protests. These protests, however, received no support by the local political elites and did not gain significant media coverage, unlike in other regions (Pettrachin, 2019). In Kingdon's words (2014, p. 113)…”
Section: Why Potential Anti-migrant Political Entrepreneurs Do Not Pomentioning
confidence: 97%
“…Many interviewees, if explicitly asked so, reported that they remembered some spontaneous anti-migrant protests. These protests, however, received no support by the local political elites and did not gain significant media coverage, unlike in other regions (Pettrachin, 2019). In Kingdon's words (2014, p. 113)…”
Section: Why Potential Anti-migrant Political Entrepreneurs Do Not Pomentioning
confidence: 97%
“…In November 2018, the 'Decree-Law on Immigration and Security'also known as the 'Salvini decree'was passed, introducing a package of 42 articles. Among other things, this abolished humanitarian protection status for migrants, reduced barriers to stripping migrants of Italian citizenship, lengthened the naturalisation process, stopped asylum seekers from accessing reception centres and introduced a fast-track expulsion system for 'dangerous' asylum seekers (Pettrachin 2020;Geddes and Pettrachin 2020). The lower house passed the bill with 396 in favour and 99 opposed.…”
Section: Salvini's Governance Of the 'Crisis': 2018-2019mentioning
confidence: 99%
“…In the above article (Pettrachin, 2019) not all information was included in the authors affiliation and the financial support statement. The correct information is below and has been updated in the original article.…”
mentioning
confidence: 99%